Norovirus immunology: Of mice and mechanisms - Newman, Kira L (Eur J Immunol, 2015)
Noroviruses (NoVs) are the most common cause of sporadic and epidemic gastroenteritis in the United States and Europe and are responsible for 20% of acute gastroenteritis worldwide. Over the past decade, the understanding of NoV immunology has grown immensely. Studies of the natural immune response to NoV in humans and animal models have laid the foundation for innovations in cell culture systems for NoV and development of new therapeutics. Evidence from animal models, NoV surrogates, observational human research, and human challenge studies suggest that the innate immune response is critical for limiting NoV infection but is insufficient for viral clearance. NoV may antagonize the innate immune response to establish or prolong infection. However, once a robust adaptive immune response is initiated, the immune system clears the infection through the action of T cells and B cells, simultaneously generating highly specific protective immunologic memory. We review here both the current knowledge on norovirus immunity and exciting new developments, with a focus on ongoing vaccine development work, novel cell culture systems, and advances in understanding the role of the gut microbiome. These changes reinforce the need for a better understanding of the human immune response to NoV and suggest novel hypotheses.